Avaliação do SPAECE nas práticas pedagógicas dos professores de matemática - Abreu, Dalmário Heitor Miranda de (2018)
This work aimed to understand the relationship between the last results of mathematics of the final years of elementary school obtained by the external evaluation, based on the Permanent System of Evaluation of Basic Education of Ceará (SPAECE), and the daily school and pedagogical practice of teachers of mathematics of the ninth year of the municipal education network of Fortaleza, Ceará. The thematic was analyzed from the perspective of the mathematics teacher. This research of predominantly qualitative approach used, as a methodological research strategy, bibliographical and documentary research, with the purpose of understanding the studied reality and establishing the typology of the schools object of the investigation. A field survey was then carried out using a semi-structured interview technique, which was carried out in four schools in the city of Fortaleza, using the comparative method. Understanding that large-scale evaluation is not the end of the educational process, but the means that can lead to the improvement of the teacher's performance in his or her pedagogical practice, including evaluative, it is necessary to consider it as a fundamental dimension of the educational process, but not as their reason for being. It was not, therefore, a denial of evaluation, either external or internal. We tried to understand the implications of the external evaluation on the pedagogical practices of mathematics teachers, in order to contribute to the development of public policies for the improvement of education, the central intention that we intend to fulfill with this work. It is worth highlighting among the results the fact that the best evaluated schools are not located in noble regions of the city, but in regions of low HDI. For teachers, the results depend more on pedagogical work than on school infrastructure and support from the Department of Education. They also complained about the excessive time that the schools have spent in preparing the SPAECE. In this sense, this research sought to unveil the reasons that are leading the evaluation to the very centrality of public education policies, as demonstrated by the teachers' speech, and the risks of such a strategy lead to evaluationism to the detriment of the broader education of the students.